PROMOTING FIX-UP STRATEGY TO IMPROVE READING COMPREHENSION AT SMP BINATAMA PALEMBANG - Ramadhona Ramadhona; Jenny Elvinna Manurung; Farnia Sari (Universitas Tridinanti Palembang, 2022)
Fix-Up strategy is an effective strategy to develop the students’ creativity in thinking and expand their knowledge because they are connecting what is stated in the text and what have been ever experienced that could help increasing their reading comprehension. The aimsof this study were to find out whether or not there was a significant improvement of students’ reading comprehension achievement through fix-up strategy and to find out whether or not there was a significant difference instudents’ reading comprehension achievement between students who were taught by using Fix-Upstrategy and those who were not. The population was the eighth-graders of SMP Binatama with total number 127.Toselectthe sample of this study, purposive sampling technique was implemented.There were 64 students as sample. The data were obtained from students’reading comprehension test in recount text. In analyzing the data,paired sample t-test and independent sample t-test were used. The result of paired sample t-test showed that t-obtained(16.435)was higher than t-table (0.296) and the results of independent sample-test showed that t-obtained (6.697) was higher than t-table (0.296). It can be concluded that there was a significant improvement of reading comprehension through Fix-Upstrategy and there was a significant difference in students’ reading comprehension between the students who were taught by using Fix-Upstrategy and those who were not.Keywords:promoting, fix-up strategy, reading comprehension